2009
DOI: 10.1075/wll.12.1.03zar
|View full text |Cite
|
Sign up to set email alerts
|

Literacy predictors and early reading and spelling skills as a factor of orthography

Abstract: The majority view of reading development maintains the importance of specific cognitive and linguistic abilities, e.g. phonological awareness (PA) and vocabulary and verbal working memory (VWM). Another factor in attaining literacy may be the language of exposure, e.g. whether it has a transparent or a deep orthography. This study examines the interaction between known predictors for literacy development and the orthography. It focuses on early levels of literacy (decoding and spelling) amongst children with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 0 publications
1
10
1
1
Order By: Relevance
“…Neither of these hypotheses was supported. In contrast to predictions made by a strong ODH (Katz & Frost, 1992;Lukatela et al, 1995) as well as fi ndings reported in previous studies (Cossu et al, 1995;Oney & Durgunoglu, 1997;Wimmer & Hummer, 1990;Zaretsky et al, 2009), the fact that unpointed Hebrew is a deep orthography did not seem to create a signifi cant word-processing disadvantage for its readers, neither in the short nor the long term or whether word-processing speed or accuracy was considered. On the contrary, Hebrew participants -as a group -actually manifested somewhat enhanced wordprocessing accuracy when determining word identicalness under conditions that required the access of conventionalised (conceptual) knowledge (C-condition).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Neither of these hypotheses was supported. In contrast to predictions made by a strong ODH (Katz & Frost, 1992;Lukatela et al, 1995) as well as fi ndings reported in previous studies (Cossu et al, 1995;Oney & Durgunoglu, 1997;Wimmer & Hummer, 1990;Zaretsky et al, 2009), the fact that unpointed Hebrew is a deep orthography did not seem to create a signifi cant word-processing disadvantage for its readers, neither in the short nor the long term or whether word-processing speed or accuracy was considered. On the contrary, Hebrew participants -as a group -actually manifested somewhat enhanced wordprocessing accuracy when determining word identicalness under conditions that required the access of conventionalised (conceptual) knowledge (C-condition).…”
Section: Discussioncontrasting
confidence: 99%
“…The validity of the ODH has been tested in several lines of research comparing reading skills of readers in two different languages. Evidence obtained from a number of these studies indeed suggests that -in comparison to counterparts learning to read in a deep orthography -learning to decode and read shallow orthographies such as German (Wimmer & Hummer, 1990), Italian (Cossu, Shankweiler, Liberman & Gugliotta, 1995), Croatian (Frost, 1989;Zaretsky, Kraljevic, Core & Lencek, 2009) and Turkish (Oney & Durgunoglu, 1997;Raman, 2006) is easier, with children making relatively few errors in the voiced decoding of words by the end of the fi rst year of formal instruction. Moreover, readers of shallow orthographies seem to exhibit a particular advantage in relation to the reading of nonsense words (NWs) (e.g., Goswami, Gombert & de Barrera, 1998;Landerl, 2000;Wimmer & Goswami, 1994), implying that their ability to use grapheme-to-phoneme correspondence knowledge for the processing of unfamiliar letter strings develops early and rapidly as they enter formal education (e.g., Wimmer & Hummer, 1990).…”
mentioning
confidence: 99%
“…Obviously, it is much easier to rely on letters as graphic representations of phonological units when these representations are consistent. In recent years, numerous cross-linguistic studies have given support to the idea that the development of at least some aspects of phonological awareness is influenced by the phonology and orthography of the language the child speaks and learns to read in (Caravolas & Bruck 1993;Bruck, Genesee & Caravolas 1997;Durgunoglu & Öney 1999;Goswami, Ziegler & Richardson 2005;Share & Blum 2005;Zaretsky et al 2009). It has also been convincingly demonstrated that in orthographically consistent languages the speed of phonemic awareness development after the onset of reading instruction progresses very rapidly, since the consistency of orthography in these languages acts as a bootstrapping device for promoting phonemic awareness (Cossu, Shankweiler, Liberman, Katz & Tola 1988;Bentin, Hammer & Cahan 1991;Wimmer & Goswami 1994;Cossu, Shankweiler, Liberman & Gugliotta 1995;Öney & Durgunoglu 1997;Frith, Wimmer & Landerl 1998;Durgunoglu & Öney 1999;Landerl & Wimmer 2000;Holopainen, Ahonen & Lyytinen 2002;Mann & Wimmer 2002;Aro 2004).…”
Section:  Introductionmentioning
confidence: 95%
“…Bulgular, çalışma içerisinde test edilen bu hipotezin doğrulandığını ve öğrencilerin sınıf düzeylerinin artmasıyla sesbilgisel çözümleme performanslarına göre zayıf okuyucu grubuna giren öğrenci sayılarının azaldığını göstermiştir (Tablo 3). Sesbilgisel çözümleme ile sözcük okuma arasındaki ilişkiye bakıldığında, alanyazında bu iki beceri arasında doğrusal bir ilişki olduğu ve sözü edilen bu ilişkinin iki beceri arasındaki karşılıklı etkileşimler sonucunda ortaya çıktığı sıkça vurgulanmaktadır (Raman ve Weekes, 2005;Zaretsky, Kraljevic, Core ve Lencek, 2009;Miller vd., 2014;Güldenoğlu vd., 2012;Kargın vd., 2011;Miller, 2004aMiller, , 2006aVaughn, Bos ve Schumm, 2003;Wauters, VanBon ve Tellings, 2006;Frost, 1998Frost, , 2006Jackson ve Coltheart, 2001;Ramus vd., 2003). Konuya ilişkin yapılan farklı çalışmalarda da öğrencilerin eğitim düzeylerinin artmasıyla daha çok okuma deneyimine sahip olacakları, bu durumun da onların harf-ses, hece-ses dönüşümleri gibi sesbilgisel çözümleme süreçlerinde ustalaşmalarını sağlayacağı sıkça vurgulanmaktadır (Beauchet vd., 2010;Güldenoğlu vd., 2012;Erdoğan, 2012;Makhoul, 2017;Steensel vd., 2016;Bowey, 1996;Kirby vd., 2008;Jackson ve Coltheart, 2001).…”
Section: Tartışma Ve Sonuçunclassified